1998
DOI: 10.1046/j.1365-2923.1998.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a continuing medical education programme in interpersonal communication skills on doctor practice and patient satisfaction in Trinidad and Tobago

Abstract: This study investigates the effects of a brief training programme on the communication skills of doctors in ambulatory care settings in Trinidad and Tobago. Evaluation of doctor performance is based on analysis of audiotapes of doctors with their patients during routine clinic visits and on patient satisfaction ratings. A pre-test/post-test quasi-experimental study design was used to evaluate the effects of exposure to the training programme. Doctors were assigned to groups based on voluntary participation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 20 publications
3
45
2
6
Order By: Relevance
“…The results of this study were less encouraging than results from other randomized controlled studies conducted in the West (Roter et al 1995;Roter et al 1998;Gerrity 1999), which suggested that Continuing Medical Programme can improve a number of physicians' communication skills towards patients who have common presentations of depression and anxiety. Our findings were also less encouraging than results from a previous study (using pre and post intervention design) conducted in Hong Kong (Chan et al 2003), where the same scale for assessing physician's consultation skills was used.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 79%
“…The results of this study were less encouraging than results from other randomized controlled studies conducted in the West (Roter et al 1995;Roter et al 1998;Gerrity 1999), which suggested that Continuing Medical Programme can improve a number of physicians' communication skills towards patients who have common presentations of depression and anxiety. Our findings were also less encouraging than results from a previous study (using pre and post intervention design) conducted in Hong Kong (Chan et al 2003), where the same scale for assessing physician's consultation skills was used.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 79%
“…For example, a growing body of research suggests that training programs for physicians may be greatly enhanced through the use of EI measures. Greco, Francis, Buckley, Brownlea, & McGovern (1998) and Roter et al (1998) demonstrated that physicians' social competence is greatly improved through well-designed training programs, which ultimately bears on the quality of health care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships characterized by higher levels of communication result in better adherence to treatment regimens and better health outcomes (Hulsman, Ros, Winnubst, & Bensing, 1999;Roter et al, 1998;Stewart, 1995). Assessment skills.…”
Section: Communication Skills Effective Communication In-mentioning
confidence: 99%